Differential effects of habitual chow-based and semi-purified diets on lipid metabolism in lactating rats and their offspring. Issue 5 (27th February 2015) - del Bas, Josep Maria; Caimari, Antoni; Ceresi, Enzo; Arola-Arnal, Anna; Palou, Andreu; Arola, Lluís; Crescenti, Anna
Abstract : Diet during pregnancy and lactation is a critical factor in relation to the health of dams and their offspring. Currently, control diets used in metabolic imprinting studies differ in composition and type, i.e. semi-purified diets (SD) or chow-based diets (ND). The aim of the present study was to determine whether two widely used control diets, a SD and a ND, that mainly differ in fat content (5·08 and 3·26 %, respectively) and its sources (soyabean oil for the SD and cereals and fish for the ND), fibre (6 and 15 %, respectively), and cholesterol (26 and 69 mg/kg diet, respectively) can influence the lipid metabolism of dams and their offspring. Wistar rats were fed either the SD or the ND during pregnancy and lactation. At weaning, SD-fed dams presented severe hepatic steatosis and increased levels of circulating TAG, NEFA and insulin. Importantly, the offspring presented an altered plasma lipid profile. In contrast, the ND allowed for a normal gestation and lactation process, and did not affect the metabolism of offspring. In parallel, virgin rats fed the SD showed no metabolic alterations. A higher intake of SFA and MUFA and a lower consumption of PUFA observed in SD-fed dams during the lactation period could contribute to explaining the observed effects. In conclusion, two different control diets produced very different outcomes in the lipid metabolism of lactating rats and their offspring. The present results highlight the importance of the assessment of the metabolic state of dams when interpreting the results of metabolic programming studies.